PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI PENERAPAN MODEL STAD MASA COVID-19 PADA SISWA SDN 1 MAMBEN DAYA KECAMATAN WANASABA TAHUN PELAJARAN 2020-2021 - HURUL’IN HURUL’IN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
This study aims to improve mathematics learning outcomes through the application of the STAD MASA Covid-19 Model to students of SDN 1 Mamben Daya, Wanasaba District, 2020-2021 Academic Year. This research method is CAR (Classroom Action Research). The subjects of the study were grade III students of SD Negeri 1 Mamben Daya, Wanasaba district, East Lombok district, for the 2020/2021 academic year, totaling 12 students and consisting of 3 male students and 9 female students with an average age of 9 years, due to the Covid-19 period. so that the research subjects were taken 12 students. Based on the results of data analysis in each cycle, it appears that the results from cycle I to cycle II have increased. In the implementation of learning and the results of the first cycle of data analysis, for student activities an average score of 3.2 was obtained and student activities in the second cycle obtained an average grade of 3.9. So it can be concluded that. the application of the STAD method can improve mathematics learning outcomes in mas COVID-19 third grade students at SDN 1 Mamben Daya for the 2020/2021 academic year. ABSTRAKPenelitian ini bertujuan untuk meningkatkan hasil belajar Matematika melalui penerapan Model STAD MASA Covid-19 pada siswa SDN 1 Mamben Daya Kecamatan Wanasaba Tahun Pelajaran 2020-2021. Metode penelitian ini adalah PTK (Penelitian Tindakan Kelas). Subyek penelitian adalah siswa kelas III SD Negeri 1 Mamben Daya kecamatan Wanasaba kabupaten Lombok Timur tahun pelajaran 2020/2021 yang berjumlah 12 siswa dan terdiri atas 3 siswa laki-laki dan 9 siswa perempuan dengan usia rata-rata 9 tahun, karena masa covid-19 sehingga subyek penelitian diambil 12 siswa. Berdasarkan hasil analisis data pada tiap siklus, terlihat bahwa hasil dari siklus I ke siklus II mengalami peningkatan. Pada pelaksanaan pembelajaran dan hasil analisis data siklus I, untuk aktivitas siswa diperoleh nilai rata-rata sebesar 3,2 dan aktivitas siswa pada siklus II diperoleh nilai rata-rata kelas sebesar 3,9. Sehingga dapat disimpulkan bahwa. penerapan metode STAD dapat meningkatkan hasil belajar matematika pada mas COVID-19 siswa kelas III SDN 1 Mamben Daya Tahun Pelajaran 2020/2021.